EXPLORING TEACHER’S PERSPECTIVES ON THE WORDWALL PLATFORM FOR ENHANCING ELEMENTARY STUDENT’S ENGLISH VOCABULARY - Jauharah Jilan Situmorang; Deasy Yunita Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore elementary school English teachers’ perspectives on the use of the Wordwall platform to enhance students’ vocabulary acquisition, highlighting the urgency of integrating digital gamification in vocabulary learning. Employing a qualitative method with a phenomenological design, the research was conducted over one month and involved three elementary school English teachers from Mis Terpadu Muhammad Fahri in North Sumatra, Indonesia, who had direct experience using Wordwall in their classrooms. Data were collected through semi-structured interviews, participatory observations, and documentation, and analyzed using the Miles and Huberman model. The findings reveal four key themes: (1) Wordwall is user-friendly and easily integrated into daily teaching; (2) it increases students' motivation and engagement; (3) it significantly improves vocabulary mastery through interactive, repetitive game-based learning; and (4) teachers apply various strategies to integrate Wordwall effectively, although they face challenges related to internet access and time constraints. In conclusion, the Wordwall platform supports vocabulary learning not only by making it more enjoyable and meaningful but also by fostering student participation and retention. This study offers valuable insights for educators and curriculum developers by highlighting Wordwall as a practical and innovative tool that can enhance the effectiveness of English vocabulary instruction in primary education.